Comparison of Two Rodent Models of Maternal Separation on Juvenile Social Behavior - Zimmerberg, Betty; Sageser, Kristin A. (Frontiers in Psychiatry, 2011)
Early childhood deprivation is associated with an increased risk of attachment disorders and psychopathology. The neural consequences of exposure to stress early in life have used two major rodent models to provide important tools for translational research. Although both models have been termed Maternal Separation, the paradigms differ in ways that clearly shift the focus of stress between maternal and offspring units. The first model, here called Early Deprivation (ED), isolates pups individually while the dam is left not alone, but with a subset of littermates in the home nest (“Stay-at-homes”). The other model, here called Maternal Separation (MS), isolates the dam in a novel cage while the pups are separated together. In this study, these two early stress models were directly compared for their effects on social behaviors in male and female juvenile offspring. Although both models altered play behavior compared to controls, patterns of prosocial behaviors versus submissive behaviors differed by model and sex. Additionally, there were main effects of sex, with female ED subjects exhibited masculinizing effects of early stress during play sessions. Maternal behavior upon reunion with the isolated subjects was significantly increased in the MS condition compared to both ED and control conditions, which also differed but by a lesser magnitude. “Stay-at-homes” were tested since some laboratories use them for controls rather than undisturbed litters; they displayed significantly different sex-dependent play compared to undisturbed subjects. These results indicate that early stress effects vary by paradigm of separation. We suggest that MS produces greater stress on the dam and thus greater maternal mediation, while ED causes greater stress on the neonates, resulting in different behavioral sequela that warrant attention when using these models for translational research.